A New Bound on the Domination Number of Graphs with Minimum Degree Two - Henning, Michael A.; Schiermeyer, Ingo; Yeo, Anders (The Electronic Journal of Combinatorics, 2011)
For a graph $G$, let $γ(G)$ denote the domination number of $G$ and let $δ(G)$ denote the minimum degree among the vertices of $G$. A vertex $x$ is called a bad-cut-vertex of $G$ if $G-x$ contains a component, $C_x$, which is an induced $4$-cycle and $x$ is adjacent to at least one but at most three vertices on $C_x$. A cycle $C$ is called a special-cycle if $C$ is a $5$-cycle in $G$ such that if $u$ and $v$ are consecutive vertices on $C$, then at least one of $u$ and $v$ has degree $2$ in $G$. We let ${\rm bc}(G)$ denote the number of bad-cut-vertices in $G$, and ${\rm sc}(G)$ the maximum number of vertex disjoint special-cycles in $G$ that contain no bad-cut-vertices. We say that a graph is $(C_4,C_5)$-free if it has no induced $4$-cycle or $5$-cycle. Bruce Reed [Paths, stars and the number three. Combin. Probab. Comput. 5 (1996), 277–295] showed that if $G$ is a graph of order $n$ with $δ(G) \ge 3$, then $γ(G) \le 3n/8$. In this paper, we relax the minimum degree condition from three to two. Let $G$ be a connected graph of order $n \ge 14$ with $δ(G) \ge 2$. As an application of Reed's result, we show that $γ(G) \le \frac{1}{8} ( 3n + {\rm sc}(G) + {\rm bc}(G))$. As a consequence of this result, we have that (i) $γ(G) \le 2n/5$; (ii) if $G$ contains no special-cycle and no bad-cut-vertex, then $γ(G) \le 3n/8$; (iii) if $G$ is $(C_4,C_5)$-free, then $γ(G) \le 3n/8$; (iv) if $G$ is $2$-connected and $d_G(u) + d_G(v) \ge 5$ for every two adjacent vertices $u$ and $v$, then $γ(G) \le 3n/8$. All bounds are sharp.